Managing the Fed's Liftoff and Transmission of Monetary Policy - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2015)
In recent years, many money and repo rates in the United States have been between zero and 25 basis points. As Fed's liftoff approaches, the question of the level of these rates (and the markets that determine them) becomes increasingly important. The paper discusses (i) whether the Fed can control short-term rates as it starts to tighten; and (ii) what are the advantages and disadvantages of using asset sales versus a large reverse repo program (RRP). A large RRP by the Fed will deprive the financial system of the money pool (i.e., GSEs and money market funds) as the Fed will directly absorb the money on to its balance sheet. This will rust the financial plumbing that connects the money pool to collateral suppliers. Some asset sales may be preferred to a large RRP as this will result in a market-determined repo rate and will allow the Fed to reach its monetary policy liftoff objectives with minimal footprint on market plumbing. We also discuss cost of issuing short tenor T-bills relative to a large RRP in a rising rate environment.